Ogo Malane Tolitoli City Drinking Water Priority Services - Tahir, Suratnan; Sulfiati, Sulfiati; Burhanuddin, Burhanuddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2019)
This research was conducted in Tolitoli Regency, from February to June 2012 Analysis of Clean Water Services for Low-Income Customers at the Tolitoli City Water Supply Company. This study aims to determine the priority service for drinking water in PDAM Ogo Malane Tolitoli City. The sample in this study was 54 heads of households from the group of low-income household customers in five villages in Tolitoli Regency that were served by the Ogo Malane Regional Water Supply Company in Tolitoli City. The entire research sample in the five villages mentioned above was determined as a research sample using random sampling techniques, namely by providing equal opportunities to every low-income customer residing in the five villages to be selected as a research sample. Data analysis tools in this study used the Spearman Rank Correlation analysis approach. The results of this study illustrate that: first, clean water services to low-income customers are considered not good at the Regional Water Supply Company Ogo Malane Tolitoli City, because the results of the study indicate the response given by the company to customer complaints is unsatisfactory. This is due to the Regional Water Supply Company. Ogo Malane Tolitoli City seems slow to respond when there are complaints from low-income customers in connection with clean water services provided by the company through the use of Public Hydrants. Second, there is a negative and significant relationship between clean water tariffs and services to low-income customers in the Regional Water Supply Company of Ogo Malane Tolitoli City. This negative relationship occurs because the clean water tariff charged by the company is considered low-income customers less than the equivalent of clean water services provided by the company through the use of Public Hydrants.